1994
DOI: 10.1007/bf00180182
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying parosteal lipoma with exuberant cortical reaction

Abstract: Lipomas lying close to bone are called parosteal lipomas. They usually cause some bone reaction. We are reporting a dramatic example of this rare condition and have discussed the differential diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Although our tumor would fit the description of osteolipoma, its attachment to the periosteum, however, would be in favor of an ossifying parosteal lipoma. Only 9 cases of ossifying parosteal lipomas have been described in the literature: 7 in the upper extremities (femur 5, humerus 2), 1 in the trunk (rib) and 1 in the mandible [43][44][45][46][47][48][49][50][51]. An underlying bone reaction was always present (uneven and undulating cortex, hyperostosis, osseous excrescences), but was absent in our report.…”
Section: Discussionmentioning
confidence: 67%
“…Although our tumor would fit the description of osteolipoma, its attachment to the periosteum, however, would be in favor of an ossifying parosteal lipoma. Only 9 cases of ossifying parosteal lipomas have been described in the literature: 7 in the upper extremities (femur 5, humerus 2), 1 in the trunk (rib) and 1 in the mandible [43][44][45][46][47][48][49][50][51]. An underlying bone reaction was always present (uneven and undulating cortex, hyperostosis, osseous excrescences), but was absent in our report.…”
Section: Discussionmentioning
confidence: 67%
“…• In 1994 in Saudi Arabia, a large-volume parosteal lipoma with exuberant hyperostosis was found in the right thigh of a young patient; however, in spite of the characteristics, the lipoma was not surgically resected. 7 • Also in 1994, another finding was published concerning this rare benign neoplasia in the femur, also with relevant reaction of bone. 3 • Genetic characteristics were shown in the article by Bridge et al 18 • Another case was reported in 1999 by Kim et al…”
Section: Discussionmentioning
confidence: 94%
“…3,6,13 These changes include bone deformity, cortical erosion, and overproduction of the cortical bone (hyperostosis). 3,[6][7][8] More than half of parosteal lipomas presenting bone reactions are associated with hyperostosis. 6 Several authors consider that cortical hyperostosis can be explained by the contact of the lipoma with the bone, 3,14 being presumably caused by stimulation or irritation of the periosteum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bone may be normal inspite of the close relationship of lipoma with the periosteum [12] [13], but reactive changes in the adjacent bone [14] such as bone deformity, cortical erosion, and bony hyperostosis [15] [16] had been detected. More than half of parosteal lipomas presenting bone reactions are associated with hyperostosis [13] [17].…”
Section: Discussionmentioning
confidence: 99%